The early years of leadership : the journey begins - Marshall, Ian A.; Jackman, Grace-Anne; Armstrong, Denise E. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"This volume is distinctive for many reasons, chief among which are a strong commitment to honouring practitioners' stories and empirical research. The chapters in this volume also represent the work of scholars and school practitioners from the global north and south. This fusion of diverse international perspectives identifies local and global trends and commonalities and provides aspiring and novice school principals with practical information and strategies related to finding their internal compass, crafting their leadership philosophy, and negotiating common leadership pitfalls inside and outside of the school community. This book is intended for use by aspiring and incumbent school administrators, professional development programmes and students enrolled in educational leadership and administration courses. Each chapter offers an overview of the specific area of focus and concludes with reflective activities and questions for discussion. It can therefore be used as a companion reader for aspiring, novice, and experienced administrators, as well as a teaching tool by universities and other professional development programmes"-- Provided by publisher.
Keywords: Educational leadership.; School management and organization.; Education -- Administration -- General.; Educational administration and organization.; elektronické knihy; electronic books